Pola Pikir Makan dan Preferensi Mahasiswa terhadap Makanan dan Minuman Jadi: Studi Kasus di Kota Bandar Lampung Saat Pandemi Covid-19 - Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah; Yaktiworo Indriani; Shinta Tantriadisti; Tyas Sekartiara Syafani (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2021)
Lifestyle is one of the factors that influence consumer behavior. The increase in spending on the consumption of food and beverage in Indonesia shows changes in people's lifestyles, including college students who like eating out. Food consumption is closely related to the eating mindset and preferences of someone. This study aims to analyze college students’ preferences of foods and beverages; analyze the student's eating mindset and analyze the correlation between college students’ eating mindset and preferences of foods and beverages in Bandar Lampung City. This research used a survey method. The data was collected from May to July 2020 (the Covid-19 pandemic period). The sampling technique used was quota sampling and the number of samples was 500 college students in Bandar Lampung City. The primary data collection was carried out using an online questionnaire. The data were analyzed by descriptive statistics and Kendall's Tau correlation test. The results showed that: (1) college students' preference of beverages was higher than foods and based on the variety, the highest preference of main course/meal was noodles, the snack was pempek and beverages were bottled mineral water; (2) the college student's eating mindset about the benefits of eating is good enough, but the consumption is still rice oriented and (3) eating mindset about the benefits of eating dimensions has a significant negative effect on the preferences of college students in Bandar Lampung City for meals made from rice and flour, and snacks made from flour and sago. College students' knowledge of food and nutrition, and also local food diversification needs to be improved to achieve the goal of food diversification.